2010
DOI: 10.4103/1596-3519.62620
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis: A retrospective analysis of clinical pattern and outcome in north western Nigeria

Abstract: Rhinosinusitis in this region was more of chronic (83.6%) variety than acute (16.4%) variety. Infective causes (67.1%) and allergy (28.8%) were the commonest etiological factors. About (86.3%) were amendable to medical treatment while surgical treatment was carried out in 13.7% of the cases. Rhinosinusitis should be managed medically first before recourse to surgical measures in carefully selected cases. Endoscopic sinonasal surgery is most desirable in keeping with current global trends of treatment of rhinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
18
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
(27 reference statements)
8
18
1
Order By: Relevance
“…Similar results was reported in another study by Aliyu et al 6 where the most common affected age group was 21 -40 years (65.3%) and mean age group was 44 years in a study by Stallman et al 7 We showed a slight preponderance of males (60%) over females (40%), which was observed in other similar studies by Dua et al (66%), 8 Iseh et al (57.5%), 9 Aliyu et al 6 (52%), Tsutomu et al, 10 while a female dominance was observed in a study by Stallman et al 7 The most common anatomical in our study was deviated nasal septum which was corroborated by other workers. 7,8,[11][12][13][14][15][16][17] The mere presence of a septal deviation does not suggest pathology.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results was reported in another study by Aliyu et al 6 where the most common affected age group was 21 -40 years (65.3%) and mean age group was 44 years in a study by Stallman et al 7 We showed a slight preponderance of males (60%) over females (40%), which was observed in other similar studies by Dua et al (66%), 8 Iseh et al (57.5%), 9 Aliyu et al 6 (52%), Tsutomu et al, 10 while a female dominance was observed in a study by Stallman et al 7 The most common anatomical in our study was deviated nasal septum which was corroborated by other workers. 7,8,[11][12][13][14][15][16][17] The mere presence of a septal deviation does not suggest pathology.…”
Section: Discussionsupporting
confidence: 90%
“…In a study by Iseh et al, 9 67.1% of the cases had sinusitis due to infection similar to our study where we found infection to be the most common cause with 44%. The signs and symptoms in our study were corroborated by other studies where in headache and nasal obstruction was most common.…”
Section: Fesssupporting
confidence: 91%
“…This is similar to the study conducted by Surapaneni H et al 20 which had reported the incidence of male candidates affected to be 60% and females 40%. Most of the previous studies performed by vinodhini P 21 , Dua et al 22 , Iseh et al 23 , Gibelli D et al 1 , had showed male preponderance with 66%, 57.5%, 52% and 63% respectively. Surapaneni H et al 20 had demonstrated that the age or gender does not play any significance for causing chronic rhinosinusitis especially with upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 89%
“…According to the definition of the RS task force, major symptoms and signs include facial pain/pressure, facial congestion/fullness, nasal obstruction/blockage (continuous or intermittent), nasal discharge/purulence, hyposmia/anosmia, purulence on nasal examination, and fever. The minor symptoms and signs include headache, fever, halitosis, fatigue, dental pain, cough, and ear/pain/pressure/fullness (12).…”
Section: Diagnosismentioning
confidence: 99%